2021
DOI: 10.3390/ijerph18126577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Everyday Discrimination and Relation with Wellbeing among Aboriginal and Torres Strait Islander Adults in Australia

Abstract: Discrimination is a fundamental determinant of health and health inequities. However, despite the high prevalence of discrimination exposure, there is limited evidence specific to Indigenous populations on the link between discrimination and health. This study employs a validated measure to quantify experiences of everyday discrimination in a national sample of Aboriginal and Torres Strait Islander (Australia’s Indigenous peoples) adults surveyed from 2018 to 2020 (≥16 years, n = 8108). It quantifies Prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…These areas deserve further investigation, using consistent and validated exposure measures. A recent study with a national sample of Indigenous adults, using a validated discrimination measure, found that those who had experienced moderate–high racial discrimination had increased prevalence of high blood pressure (24% higher), high cholesterol (17% higher), diabetes (57% higher) and heart disease (52% higher), than those with no discrimination [ 95 ]. Evidence about other potential social determinants during childhood and adolescence is largely lacking and a comprehensive investigation of these factors is required so that the underlying drivers of inequities in cardio-metabolic disease for Indigenous people can be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…These areas deserve further investigation, using consistent and validated exposure measures. A recent study with a national sample of Indigenous adults, using a validated discrimination measure, found that those who had experienced moderate–high racial discrimination had increased prevalence of high blood pressure (24% higher), high cholesterol (17% higher), diabetes (57% higher) and heart disease (52% higher), than those with no discrimination [ 95 ]. Evidence about other potential social determinants during childhood and adolescence is largely lacking and a comprehensive investigation of these factors is required so that the underlying drivers of inequities in cardio-metabolic disease for Indigenous people can be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on a plausible biological pathway (discrimination leading to stress and other CVD-related outcomes), the large point estimate of the effect size in a bivariate analysis and ambiguity in the literature. Furthermore, discrimination is associated with a broad range of poor health outcomes among Indigenous peoples, including commercial tobacco use, blood pressure, heart disease and diabetes, and is a fundamental determinant of health and health inequities (Thurber et al, 2021). This finding has important implications for healthcare delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The myriad of social/political factors that impact the health and well-being of Aboriginal and Torres Strait Islander people is well-documented and essential to keep in mind as we evolve digital health technology. Some of the social/political factors impacting Aboriginal and Torres Strait Islander health include racism and marginalisation 5 7 ; entrenched inter-generational trauma 8 ; discrimination 9 ; inequalities in society 10 ; disconnection from community and country 5 the historic and ongoing effects of colonisation 5 , 6 , 8 which contributes to distrust and subsequent reluctance to access services. 11 In addition, factors specific to the health system include lack of access to health care services 12 ; inadequate access to culturally competent health carers 6 , 13 which contributes to low trust and a reluctance to ask questions or even seek health services 11 creating additional barriers to self-management.…”
Section: Introductionmentioning
confidence: 99%